Cybernetics and Automation Control Theory Methods in Intelligent Algorithms : Proceedings of 8th Computer Science On-line Conference 2019, Vol. 3 /: Proceedings of 8th Computer Science On-line Conference 2019, Vol. 3. (2019) - Unknown
No abstract available